Detection of Trypanosoma cruzi in blood specimens of chronic chagasic patients by polymerase chain reaction amplification of kinetoplast minicircle DNA: comparison with serology and xenodiagnosis. - Avila, H A (1993)
A panel of 114 blood samples from chronic chagasic patients and nonchagasic patients was screened for Trypanosoma cruzi by xenodiagnostic, serologic, and polymerase chain reaction (PCR) amplification tests. Blood samples were preserved in a guanidine-EDTA buffer, and total blood DNA was isolated after chemical nuclease cleavage with 1,10-phenanthroline-copper ion and used as a template for PCR amplification of the conserved and variable regions of T. cruzi minicircle molecules. The PCR products were screened by Southern blot hybridization with a digoxigenin-labeled oligonucleotide probe specific for the conserved region of the minicircle. The method showed a sensitivity of 100% compared with the serologic test. In addition, all of the serology-positive, xenodiagnosis-negative samples were positive by PCR. This demonstrates that PCR amplification of T. cruzi kinetoplast minicircle DNA could replace xenodiagnosis for evaluation of parasitemia in chronic chagasic patients and could serve as a complement for serologic testing in the screening of blood bank donors.